Towards a Sustainable Future: Investigating Smartphone Recycling Intentions Among Saudi University Students - Baeshen, Yasser (European Journal of Sustainable Development, 2025)
This extant research aimed to explore the Saudi university students’ attitudes and behaviors of towards smartphone recycling, using the Theory of Planned Behavior (TPB) model as the theoretical framework for proposed research model. Data was collected through a questionnaire, and 850 sample respondents were selected by convenience sampling method. The study assessed five hypotheses to determine participants’ attitudes, subjective norms, perceived behavioral control, awareness of consequences and smartphone recycling intentions. Results show that while students generally held positive attitudes toward recycling, subjective norms, perceived behavioral control, and awareness of consequences emerged as the strongest predictors of recycling intentions. However, recycling intention did not significantly predict resell behavior, likely due to data privacy concerns. The findings highlight the role of cultural and normative influences in shaping recycling behavior in Saudi Arabia, a collectivist setting. This research contributes novel, policy-relevant evidence aligned with Vision 2030 goals on sustainability and circular economy development, offering practical insights for designing campus recycling programs, incentive mechanisms, and digital awareness campaigns to reduce the intention–behavior gap. Keywords: Smartphone recycling, E-waste management, Sustainability, Consumer Behavior, Disposal attitude, Resell, Saudi Arabia.